Salvia sclarea L.-mediated synthesis of silver nanoparticles: characterization, secondary metabolite influence, and antibacterial activity assessment - Arslan, Elif; Yuca, Esra; Servi, Huseyin; Pelit Arayici, Pelin; Erisen, Semiha (IOP Publishing Ltd, 2025)
Silver nanoparticles (AgNPs) have demonstrated significant potential for a range of applications, particularly in the field of agriculture, owing to their unique properties. As an alternative to conventional chemical methods, the green synthesis approach, involving the use of plant extracts, has gained attention due to its environmentally friendly and cost-effective nature. In the current study, AgNPs were synthesized utilizing the leaf extract of Salvia sclarea L. as a reducing and stabilizing agent. UV-visible spectroscopy revealed a characteristic surface plasmon resonance peak at similar to 449 nm, confirming nanoparticle formation. X-ray diffraction (XRD) analysis verified the face-centered cubic (FCC) crystalline structure with distinct peaks at 2 theta values of 38.0426 degrees, 44.2132 degrees, 64.4185 degrees, and 77.3521 degrees, corresponding to the (111), (200), (220), and (311) planes, respectively. Transmission electron microscopy (TEM) showed spherical nanoparticles ranging from 2.4 to 30.6 nm, with an average size of 12.9 nm. Scanning electron microscopy (SEM) confirmed their uniform morphology. FTIR spectroscopy identified functional groups such as hydroxyl (-OH), carbonyl (C=O), and ether (C-O-C), suggesting phytochemicals' involvement in nanoparticle stabilization. Moreover, the incorporation of AgNPs into S. sclarea tissue culture media significantly altered the secondary metabolite profile of in vitro shoots, fatty acid and n-alkane derivatives were the dominant groups of the extracts. Octadecanic acid, nonacosene, heptacosene, and dotriacontane were the main compounds of the extracts. Additionally, the antimicrobial activity of the AgNPs against common bacterial strains, including Staphylococcus aureus and Escherichia coli, was evaluated. Encouragingly, the AgNPs exhibited moderate antimicrobial properties, suggesting their potential utilization in combating bacterial pathogens. This study highlights the efficacy of utilizing S. sclarea extract for the green synthesis of AgNPs, emphasizing the multifaceted nature of these nanoparticles, from their structural and chemical characteristics to their antimicrobial potential. The environmentally friendly and sustainable approach presented here holds promise for a variety of applications where AgNPs can enhance secondary metabolite production and counteract microbial threats.
Keywords: clary sage; metal nanoparticles; biosynthesis; elicitor; silver nitrate; reduction; GENE-EXPRESSION; GREEN SYNTHESIS; EMBRYOGENESIS; GROWTH; PLANTS; Science & Technology - Other Topics; Materials Science; Physics